2023
DOI: 10.7150/ijbs.79482
|View full text |Cite
|
Sign up to set email alerts
|

B cells in tumor metastasis: friend or foe?

Abstract: Metastasis is an important cause of cancer-related death. Immunotherapy may be an effective way to prevent and treat tumor metastasis in the future. Currently, many studies have focused on T cells, whereas fewer have focused on B cells and their subsets. B cells play an important role in tumor metastasis. They not only secrete antibodies and various cytokines but also function in antigen presentation to directly or indirectly participate in tumor immunity. Furthermore, B cells are involved in both inhibiting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Previously, it was shown that INHBA and CCL19 exhibit opposite modes of expression in colon cancer, with INHBA being upregulated while CCL19 is concurrently downregulated ( 43 ). As CCL19 is known to be a B-cell chemoattractant ( 44 ), this could possibly predate the low levels of B-cell tumor infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that INHBA and CCL19 exhibit opposite modes of expression in colon cancer, with INHBA being upregulated while CCL19 is concurrently downregulated ( 43 ). As CCL19 is known to be a B-cell chemoattractant ( 44 ), this could possibly predate the low levels of B-cell tumor infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the staining of the mouse lungs for B cells indicated a significant increase in vaccine-induced infiltration of B cells. While we speculate that the detected B cells are vaccine-induced with the capacity to reduce the tumors’ size, further evaluations are ongoing to examine whether the detected B cells are PD-L1-positive, i.e., regulatory B cells, which have been reported in various cancers [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%